Exploring Adherence, Treatment Experiences, and Quality of Healthcare Services in HIV Management Among Iraqi Patients: Challenges and Influential Factors - Talabani SN; Mikhael EM (HIV/AIDS: Research and Palliative Care, 2025)
Shlova Najim Talabani,1 Ehab Mudher Mikhael2 1Naser Hospital, Directorate of Health - Kirkuk, Iraqi Ministry of Health, Kirkuk, Iraq; 2Clinical Pharmacy Department, College of Pharmacy, University of Baghdad, Baghdad, IraqCorrespondence: Ehab Mudher Mikhael, Email ihab.maddr@copharm.uobaghdad.edu.iqBackground: Although all antiretroviral therapies reduce viral load, first-line regimens vary slightly in effectiveness and tolerability, often leading to treatment changes. Non-adherence is common in developing countries due to limited-resources and poor patient-provider communication. Data on HIV treatment and adherence are scarce in Iraq.Objective: To obtain in-depth insight into treatment regimens, medication adherence, healthcare quality, and the challenges and factors influencing them among Iraqi HIV patients.Methods: A qualitative study utilizing face-to-face interviews was conducted with HIV patients at three HIV centers in Iraq. The interview-guide was developed and validated by a panel of experts. Participants were recruited via convenience and purposive sampling. Interviews, conducted in Arabic, were audio-recorded and lasted 10– 20 minutes. Data collection continued until saturation. Data analyzed manually by thematic-analysis approach.Results: Forty-seven HIV patients were interviewed. Three themes emerged: treatment of HIV, adherence to anti-HIV medications, and accessibility and quality of care for HIV patients. All patients were on a combination pill (Tenofovir-disoproxil, lamivudine, and dolutegravir), but most had changed regimens due to medication shortages or side effects. While most began treatment immediately after diagnosis, delays occurred mainly due to administrative issues, drug unavailability, or side effects. Most patients reported transient initial side effects. Medication adherence was generally good, though many patients missed some doses due to forgetfulness, travel, or medication unavailability. Most patients rated care quality as good, valuing the physician’s role in HIV-management. Barriers to accessing care included medication supply interruption and discrimination. Recommendations to improve care included establishing specialized clinics at HIV centers and ensuring continuous medication supply.Conclusion: HIV care in Iraq largely aligns with international guidelines, but administrative delays hinder timely treatment initiation. Adherence is good, though medication supply interruptions and travel are main non-adherence factors. Ensuring continuous medication supply and establishing specialized clinics are essential for improved care.Plain language summary: Most HIV patients in Iraq are taking a single daily pill called TLD, but many have changed their treatment due to medications’ shortages or side effects.Patients mostly start treatment quickly after diagnosis, but some face delays because of administrative issues or fear of side effects.Medication side effects are common but usually temporary; most patients follow their treatment well, though some miss doses.Patients rate the quality of care as good, but face barriers like medicine shortages, discrimination, and difficulty accessing services outside clinics.To improve HIV care, recommendations include ensuring continuous medication supply, creating special clinics, and protecting patient privacy to reduce stigma.Keywords: human immunodeficiency virus, treatment, medication adherence, Iraq